Population norms for quality adjusted life years for the United States of America, China, the United Kingdom and Australia. (21st May 2021) - Palmer, Andrew J.; Campbell, Julie A.; de Graaff, Barbara; Devlin, Nancy; Ahmad, Hasnat; Clarke, Philip M; Chen, Mingsheng; Si, Lei
Abstract: Health economics uses quality adjusted life years (QALYs) to help healthcare decision makers. However, unlike life expectancy for which age‐ and sex‐dependent national life tables are available, no general population norms exist to use as a benchmark against which to compare observed or modeled projections of QALYs in sub‐populations or patients. We developed a 2‐state Markov model to generate QALY population norms for the USA, UK, China and Australia. Annual age‐ and sex‐specific probabilities of all‐cause mortality were taken from life tables combined with general population country‐specific age‐ and sex‐specific health state utilities for the EQ‐5D‐3L (all countries); and SF‐6D (Australia) multi‐attribute utility instruments (MAUI). To validate our QALY benchmark model we found that the model closely predicted population life expectancies. Using EQ‐5D‐3L, undiscounted QALYs for males/females aged 18 years ranged 54.62/58.90 (USA), 55.55/60.21 (China), 57.11/60.16 (Australia), and 58.01/61.43 (UK) years. SF‐6D benchmark QALYs for Australia were consistently lower than those generated from the EQ‐5D‐3L. The gap in undiscounted QALYs between the UK (highest) and the USA (lowest) was 2.53 QALYs in women and 3.39 QALYs in men aged 18 years. Our model's QALY population norms can be used for internal validation of future health economic models for the country‐specific value sets for the instruments that we adopted, and when quantifying burden of disease in terms of QALYs lost due to illness compared to the general population. We have created a publicly available repository to continuously include QALY benchmarks that use country‐specific value sets for other MAUIs and life expectancies.